Climate Change at the International School of Kenya - Singh, Hazel (FORUM, 2020)
This article is about the efforts of Students for the Environment, which operates at the International School of Kenya. It discusses their past successes, their current plans and what they hope for the future. It includes their operations, as well as the impact they have been able to have on their school community. It also introduces some of the ways they plan to positively affect their environment, mitigate negative impacts on their environment and how it contributes to climate change.
Keywords: C:Kenya; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:kenya; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found